PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH MANDIRI MITRA USAHA CABANG AMPANA - Abdul Malik (Katalogis, 2018)
Customer satisfaction is an important aspect in improving the quality of service so that the service can be received with optimal level of satisfaction. Quality is the core of institutional survival, which means that the survival of an institution is determined by the quality of its products. The movement of the quality revolution through an integrated quality management approach becomes a demand that should not be ignored. The movement aims to improve the quality of products on an ongoing basis for the interests of stakeholders. The study aims to determine the influence of service quality includes: physical evidence, empathy, reliability, responsiveness, and certainty simultaneously and partially to the satisfaction of Mandiri Mitra Ampana Branch customers. The result of multiple linear regressions is concluded that the quality of service namely physical evidence, empathy, reliability, responsiveness, and certainty, simultaneously and partially significant effect on customer satisfaction of Mandiri Mitra Usaha Branch Ampana.